Suberites syringella ... - Morozov, Grigori; Strelkova, Natalya Anisimova; Zimina, Olga; Sabirov, Rushan (Zenodo, 2023)
Suberites syringella (Schmidt 1868) (Fig. 5a–d) Raspalia syringella: Schmidt 1868, p. 10, pl. II, fig. 9; Topsent 1938, p. 13. Suberites spec.: Vosmaer 1885, p. 21, pl. I, fig. 9a,b; pl. IV, fig. 33. Suberites glabra: Hansen 1885, p. 11, pl. II, fig.9. Suberites carnosus var. ramosus: Topsent 1900, p. 237, pl. VII, figs. 1, 2; Lundbeck 1909, pp. 453–454; Breitfuss 1911, p. 218; Breitfuss 1912, p. 74; Topsent 1913, p. 26; Topsent 1928, p. 155; Koltun 1964, p. 150; Rezvoi 1928, p. 82. Suberites carnosus: Hentschel 1929, p. 926. Pseudosuberites carnosus: Koltun 1966, p. 99, fig. 72, pl. XXXIII, figs. 3–4. Suberites syringella: Pulitzer-Finali 1978, pp. 24–25, figs. 2–3; Pulitzer-Finali 1983, p. 483; Voultsiadou-Koukoura and Van Soest 1993, pp. 182–183; Bertolino et al. 2015, pp. 1372–1373, figs. 2B,C & 3A–C. Material analyzed. Barents Sea, PINRO trawl survey, F. Nansen, 2005, st. 4 (78.0132N, 9.9735E), depth 163 m, temperature 3.93 °C, salinity 35.053 psu (9 specimens; KFU-LH-2/014); st. 16 (76.6442N, ... : Published as part of Morozov, Grigori, Strelkova, Natalya Anisimova, Zimina, Olga & Sabirov, Rushan, 2023, A preliminary account of the Arctic / Subarctic Suberites (Porifera: Demospongiae) fauna, pp. 50-70 in Zootaxa 5357 (1) on pages 60-63, DOI: 10.11646/zootaxa.5357.1.2, http://zenodo.org/record/10012504 ...